Phenomorphological Characterization of Vegetable Soybean Germplasm Lines for Commercial Production. Issue 3 (1st May 2015) - Williams, Martin M.
ABSTRACT: Growing demand for vegetable soybean [ Glycine max (L.) Merr.] has renewed interest in producing the crop in the United States, a significant importer of vegetable soybean despite being the world's largest producer and exporter of grain‐type soybean. Field studies were conducted over 3 yr to(i) compare phenomorphological traits of vegetable and grain‐type soybean and (ii) identify candidate lines for vegetable soybean production in the North Central United States, the nation's leading soybean‐producing region. A total of 136 vegetable soybean entries from 22 sources were compared to 14 grain‐type cultivars representing a range of maturity groups. Germination and emergence of vegetable soybean were poorer than grain‐type entries. Seedling growth traits and rate of phenological development were higher in vegetable soybean. However, by the time of crop harvest (i.e., R6 growth stage), vegetable soybean produced shorter, smaller plants than grain‐type soybean. Seed mass accounted for some of the variation in emergence and seedling traits. Filtering entry responses by criteria essential to viable commercial production, including a sensory evaluation, 12 entries from eight seed sources were identified as the most promising candidate lines for use in the North Central United States. By comparing vegetable soybean responses to grain‐type soybean, this work puts into perspective the agronomic performance of vegetable soybean germplasm available to growers in the United States and points to specific areas of future research and crop development.